The efficacy of the manual circumlaryngeal therapy for muscle tension dysphonia: a systematic review and meta-analysis - Latoszek, Ben Barsties von; Watts, Christopher R.; Hetjens, Svetlana (The laryngoscope, 2024)
Objective Muscle tension dysphonia (MTD) is the most common functional voice disorder. Behavioral voice therapy is the front-line treatment for MTD, and laryngeal manual therapy may be a part of this treatment. The objective of this study was to investigate the effect of manual circumlaryngeal therapy (MCT) on acoustic markers of voice quality (jitter, shimmer, and harmonics-to-noise ratio) and vocal function (fundamental frequency) through a systematic review with meta-analysis. Data Sources Four databases were searched from inception to December 2022, and a manual search was performed. Review Methods The PRISMA extension statement for reporting systematic reviews incorporating a meta-analysis of health care interventions was applied, and a random effects model was used for the meta-analyses. Results We identified 6 eligible studies from 30 studies (without duplicates). The MCT approach was highly effective on acoustics with large effect sizes (Cohen's d > 0.8). Significant improvements were obtained in jitter in percent (mean difference of −.58; 95% CI −1.00 to 0.16), shimmer in percent (mean difference of −5.66; 95% CI −8.16 to 3.17), and harmonics-to-noise ratio in dB (mean difference of 4.65; 95% CI 1.90-7.41), with the latter two measurements continuing to be significantly improved by MCT when measurement variability is considered. Conclusion The efficacy of MCT for MTD was confirmed in most clinical studies by assessing jitter, shimmer, and harmonics-to-noise ratio related to voice quality. The effects of MCT on the fundamental frequency changes could not be verified. Further contributions of high-quality randomized control trials are needed to support evidence-based practice in laryngology. Laryngoscope, 134:18-26, 2024